2003
DOI: 10.1186/1471-2407-3-29
|View full text |Cite
|
Sign up to set email alerts
|

Tobacco, alcohol, and p53 overexpression in early colorectal neoplasia

Abstract: Background: The p53 tumor suppressor gene is commonly mutated in colorectal cancer. While the effect of p53 mutations on colorectal cancer prognosis has been heavily studied, less is known about how epidemiologic risk factors relate to p53 status, particularly in early colorectal neoplasia prior to clinically invasive colorectal cancer (including adenomas, carcinoma in situ (CIS), and intramucosal carcinoma).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
1

Year Published

2006
2006
2014
2014

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 26 publications
2
9
1
Order By: Relevance
“…Additionally, both smoking and alcohol have been associated with expression of the tumor suppressor gene p53. Terry et al demonstrated that alcohol intake was associated with p53 over-expression while smoking may be inversely related to p53 expression (30). In our study, the finding of decreased odds of having an adenoma with increased alcohol consumption among those who had smoked for 15 years or more could be related to the independent effects of both agents on the various oncogenes or tumor suppressors that play a role in colorectal carcinogenesis.…”
Section: Discussionsupporting
confidence: 54%
“…Additionally, both smoking and alcohol have been associated with expression of the tumor suppressor gene p53. Terry et al demonstrated that alcohol intake was associated with p53 over-expression while smoking may be inversely related to p53 expression (30). In our study, the finding of decreased odds of having an adenoma with increased alcohol consumption among those who had smoked for 15 years or more could be related to the independent effects of both agents on the various oncogenes or tumor suppressors that play a role in colorectal carcinogenesis.…”
Section: Discussionsupporting
confidence: 54%
“…Terry et al found that heavy cigarette smoking was associated with CRC cases that did not overexpress TP53 (OR = 1.7 for current smokers and OR = 1.8 for 30 or more years of smoking) (12). While data from our study appear to be consistent with those reported by Terry et al, our relative risk estimates for CS-related variables were generally lower, and not statistically significant.…”
Section: Methodsmentioning
confidence: 99%
“…With respect to CRC risk assessment, our group and others have observed differential associations between common environmental exposures, including cigarette smoking (CS), hormone therapy (HT) and folate intake (FI), and incident CRCs defined by microsatellite instability (MSI), CpG island methylator phenotype (CIMP), KRAS mutation, or BRAF mutation status (5-10). However, to date, relatively fewer studies have examined subtype-specific CRC risks by TP53 expression levels (11-12). …”
Section: Introductionmentioning
confidence: 99%
“…Thus far, to the best of our knowledge, few studies have examined associations between smoking and genetic alterations present in precancerous lesions, focusing on APC [36] and KRAS [37,38] mutations and p53 expression [39]. Therefore, further studies are necessary to establish the genetic profi le of the polyps related to smoking.…”
Section: Introductionmentioning
confidence: 98%